Sealing compound for packaging and preparation method thereof
By combining the modified polyacrylic resin emulsion and natural rubber emulsion, a sealing glue with excellent bonding performance was prepared, which solved the problems of environmental pollution, complex operation, high cost and unstable bonding performance in the use of the existing sealing glue, and achieved a sealing glue with high strength, good temperature resistance and environmental protection.
Patent Information
- Application Number
- CN202510067735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During use, existing sealing glues have problems such as environmental pollution, complex operation, high cost and unstable bonding performance, which are difficult to meet many bonding requirements, especially in special occasions such as low temperature environments and food packaging.
A sealing glue with excellent bonding performance is prepared by using modified polyacrylic resin lotion, natural rubber lotion and various additives through specific formulas and process steps. The sealing glue improves cohesion strength and bonding properties through the combination of modified nano SiO2 and functional monomers, and improves the aging performance of high and low temperatures through the addition of natural rubber.
It realizes the sealing glue with strong adhesive holding power, high bonding strength, good temperature resistance, short drying time and environmentally friendly and pollution-free. It is suitable for the bonding between the edges and bottoms of various packaging boxes, and is low in cost, and is suitable for large-scale production.
Smart Images

Figure BDA0005244753540000051 
Figure BDA0005244753540000091 
Figure BDA0005244753540000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing glue, in particular to a sealing glue for packaging and a preparation method thereof. Background Art
[0002] As an important auxiliary material, sealing glue plays a vital role in the packaging process. It can firmly bond the edges of packaging materials together to ensure the integrity of the packaging. Whether it is a paper box, a plastic box, a can or other forms of packaging, sealing glue can provide a reliable sealing effect and is widely used in the sealing, sealing and fixing of various packaging materials; sealing glue is also called overlapping glue, edge sealing glue, paper-plastic adhesive, etc. There are many types of traditional sealing glue, but these sealing glues have some problems in the use process, such as environmental pollution, operation complexity, high cost and unstable bonding performance; therefore, the development of an environmentally friendly, efficient and low-cost sealing glue has become an urgent problem to be solved in the packaging industry.
[0003] Since the shapes of packaging boxes and bags are different, some packaging materials are required to withstand the test of low temperature and meet the requirements of refrigerated transportation. Food packaging boxes require sealing adhesive products to have no toxic residue, tasteless and colorless, so sealing adhesive should be a product with a wide range of uses or able to meet multiple bonding requirements. Although traditional sealing adhesives such as oily adhesives have advantages such as strong initial adhesion and fast drying time, their toxicity and safety issues are becoming increasingly prominent. Oily sealing adhesives not only pollute the environment, but also harm the health of operators; although hot melt adhesives are environmentally friendly products, their use efficiency is low and can only be used in some manual work. It is difficult to meet the needs of large-scale paper box packaging processes. In addition, the cost of hot melt adhesives is high, which increases the packaging cost; water-based sealing adhesives generally have problems such as slow drying speed and low bonding strength. Especially for difficult-to-bond materials such as glazing technology, ordinary water-based sealing adhesives are difficult to achieve good bonding effects.
[0004] Water-based polyacrylate adhesives are environmentally friendly new products with broad application prospects due to their easy synthesis and good stability. For example, Patent No. CN102533181B discloses a sealing adhesive and a preparation method thereof, which has the advantages of low cost, no pollution, strong initial adhesion, and good adhesion to products such as calendering and lamination. However, the formula of the sealing adhesive contains a variety of raw materials, such as hard monomers, soft monomers, functional monomers, etc. The types and quantities of these raw materials are large, which may make the preparation process complicated and difficult to control, and the lasting adhesion is poor, which is not suitable for large-scale use. Since the existing polyacrylate emulsion has the disadvantages of being sticky when hot and brittle when cold, it has the problems of low bonding strength and poor adaptability to the surface energy of the substrate (it cannot stick once the surface energy is lower than 30 dynes) when sealing some plastic films without benzene solvents and low surface energy, which severely limits its application in some food and medicine packaging. The present application uses polyacrylate emulsion as the main body, and is further combined with modified polyacrylate emulsion, natural rubber emulsion and various additives to prepare a sealing glue with excellent bonding performance, thereby broadening the application of the sealing glue in the packaging field. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sealing adhesive for packaging and a preparation method thereof. The sealing adhesive has strong adhesive holding power, high bonding strength, good temperature resistance, short drying time and is environmentally friendly and pollution-free.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a sealing adhesive for packaging is carried out according to the following steps:
[0008] Step (1), adding 4-6g of sodium dodecyl sulfate and 200-300mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stirring to dissolve, adding 20-30g of vinyl acetate, 100g of butyl acrylate, 5-8g of acrylic acid, 12-15g of sodium allyloxyhydroxypropyl sulfonate and 2-10g of alkenyl cyanide modified SiO2, stirring evenly at 50-70°C, adding 3-8g of ammonium persulfate aqueous solution dropwise, then reacting at 75-90°C for 3-5h, cooling to 40-50°C, adding ammonia water to adjust the pH to 7-8, and obtaining a modified polyacrylic acid resin emulsion.
[0009] Step (2), adding 100g of polyacrylate emulsion and 5-25g of modified polyacrylic acid resin emulsion into a beaker, stirring at 800-1000r / min for 5-10min, adding 0.2-0.5g of defoamer, 15-20g of terpene resin and 10-15g of natural rubber emulsion, continuing stirring for 15-20min, adding 0.1-0.3g of wetting agent and 0.05-0.08g of preservative, stirring evenly, and obtaining a sealing adhesive for packaging.
[0010] Preferably, the mass fraction of the ammonium persulfate aqueous solution in step (1) is 5-10%.
[0011] Preferably, in step (2), the wetting agent is a mixture of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene ether in a mass ratio of 1:1.
[0012] Preferably, the main component of the natural rubber latex in step (2) is cis-1,4-polyisoprene, accounting for 91-94%.
[0013] Preferably, the preparation method of alkenyl cyanide-modified SiO2 in step (1) is carried out according to the following steps:
[0014] Step S1, under a nitrogen atmosphere, add α-cyanocinnamic acid, thionyl chloride and 1-2 drops of N,N-dimethylformamide to a reaction flask, react at 60-80° C. for 2-5 hours, remove excess thionyl chloride under reduced pressure, then add tetrahydrofuran and stir evenly, add bis[3-(trimethoxysilyl)propyl]amine and triethylamine, stir and react, after the reaction is completed, extract with chloroform and deionized water, concentrate the organic phase, and dry to obtain an alkenyl cyanosiloxane monomer.
[0015] Step S2, under a nitrogen atmosphere, add nano-SiO2, ethanol and deionized water to a reaction flask, and after uniform dispersion, add vinyl cyanosiloxane monomer, adjust the system pH to 3-5 with glacial acetic acid, stir and react, and after the reaction is completed, filter, wash, and dry under reduced pressure to obtain vinyl cyanide-modified SiO2.
[0016] Preferably, in step S1, the ratio of Α-cyanocinnamic acid, thionyl chloride, tetrahydrofuran, bis[3-(trimethoxysilyl)propyl]amine, and triethylamine is 1 g:(8-12) g:(10-15) mL:(2.2-2.5) g:(0.9-1.2) g.
[0017] Preferably, in step S1, the reaction temperature is 40-60° C. and the reaction time is 12-24 h.
[0018] Preferably, in step S2, the ratio of nano-SiO2, ethanol, deionized water, and vinyl cyanosiloxane monomer is 1 g: (8-12) mL: (2-3) mL: (0.05-0.09) g.
[0019] Preferably, in step S2, the reaction temperature is 50-65° C. and the reaction time is 5-12 h.
[0020] By adopting the above technical solution, the beneficial effects of the present invention are:
[0021] (1) The modified nano-SiO2 in the modified polyacrylic resin emulsion has a special structural hierarchy, showing a special quantum size effect and surface effect, with a large specific surface area, high surface energy and surface binding energy, which can increase the cohesive strength of the sealing glue. At the same time, since the modified nano-SiO2 is chemically bonded with the acrylic monomer, it can stably exist inside the sealing glue and has good binding properties. When subjected to external stress, it can inhibit crack growth, thereby greatly improving the bonding performance of the sealing glue. Since the functional monomers with functional groups such as carboxyl, sulfonic acid, and cyano in the polyacrylate emulsion can generate hydrogen bonds with the surface of the substrate after polymerization and undergo a certain degree of cross-linking, the cohesive strength and bonding performance of the polymer are greatly improved. At the same time, the cyano group is a strong polar group with great molecular polarity and intermolecular attraction. After the cyano group is introduced into the polyacrylate emulsion, intermolecular hydrogen bonds can be formed, which appropriately increases the toughness and improves its bonding strength, so that the prepared sealing glue can be applied to more packaging occasions.
[0022] (2) In the formulation of the sealing adhesive of the present application, some natural rubber latex is appropriately added, and there are a large number of double bonds and hydrogen bonds in its molecular chain, which can react with the functional groups on the non-polar substrate to form a strong chemical bond, thereby improving the high and low temperature aging performance of the sealing adhesive; the surface of the nano-SiO2 modified with the vinyl cyanosiloxane monomer constitutes a soft interface layer, and its compatibility with the polymer matrix is significantly improved, and it can be better dispersed and stably present. When subjected to external temperature changes, it can absorb deformation energy under the action of stress and promote the brittle-tough transition of the matrix, thereby having an enhancing and toughening effect, which helps to improve the high and low temperature resistance of the sealing adhesive.
[0023] (3) Compared with the prior art, the sealing adhesive prepared in the present application has low cost, is environmentally friendly and pollution-free, has strong initial adhesion and good lasting adhesion; has a fast drying time, high bonding strength, is less affected by the environment, and can withstand high and low temperatures. It is suitable for the bonding of edge sealing such as the edges and bottoms of various packaging boxes, and has good bonding properties for various types of packaging boxes, laminating and other products. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Natural rubber latex: The main component is cis-1,4-polyisoprene, accounting for 91-94%, and the rest is protein, fatty acids, ash, sugars, etc., purchased from Shenzhen Yoshida Chemical Co., Ltd.
[0026] α-Cyanocinnamic acid, CAS number is 1011-92-3.
[0027] Bis[3-(trimethoxysilyl)propyl]amine, CAS number is 82985-35-1.
[0028] Sodium allyloxyhydroxypropyl sulfonate, CAS number is 52556-42-0.
[0029] Example 1
[0030] (1) Under nitrogen atmosphere, 35 g of α-cyanocinnamic acid, 350 g of thionyl chloride and 42 drops of N,N-dimethylformamide were added to a reaction flask, and the mixture was reacted at 70° C. for 4 h. Excess thionyl chloride was removed under reduced pressure, and then 490 mL of tetrahydrofuran was added and stirred evenly. 84 g of bis[3-(trimethoxysilyl)propyl]amine and 37.8 g of triethylamine were added, and the mixture was reacted at 50° C. for 16 h. The mixture was extracted with chloroform and deionized water, and the organic phase was concentrated and dried to obtain an alkenyl cyanosiloxane monomer. The preparation reaction formula is as follows:
[0031]
[0032] (2) Under a nitrogen atmosphere, 30 g of nano-SiO2, 330 mL of ethanol and 75 mL of deionized water were added to a reaction flask. After uniform dispersion, 1.75 g of vinyl cyanosiloxane monomer was added, and the pH of the system was adjusted to 4 with glacial acetic acid. The reaction was carried out at 55 °C for 9 h. After filtering, washing and drying under reduced pressure, vinyl cyano-modified SiO2 was obtained.
[0033] (3) Add 5 g of sodium dodecyl sulfate and 280 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of vinyl acetate, 100 g of butyl acrylate, 7 g of acrylic acid, 14 g of sodium allyloxyhydroxypropyl sulfonate and 2 g of vinyl cyanide-modified SiO2, stir evenly at 60°C, add 5 g of an 8% by mass aqueous solution of ammonium persulfate dropwise, then react at 85°C for 4 h, cool to 45°C, add aqueous ammonia to adjust the pH to 7, and obtain a modified polyacrylic acid resin emulsion.
[0034] (4) 100 g of polyacrylate emulsion and 5 g of modified polyacrylic acid resin emulsion were added to a beaker, stirred at 900 r / min for 8 min, 0.3 g of defoamer BYK-088, 18 g of terpene resin and 12 g of natural rubber emulsion were added, stirring was continued for 16 min, 0.2 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.06 g of preservative JB11 were added, and after stirring evenly, a sealing adhesive for packaging was obtained.
[0035] Example 2
[0036] (1) Under a nitrogen atmosphere, 60 g of α-cyanocinnamic acid, 480 g of thionyl chloride and 60 drops of N,N-dimethylformamide were added to a reaction flask, and the mixture was reacted at 80° C. for 2 h. Excess thionyl chloride was removed under reduced pressure, and then 600 mL of tetrahydrofuran was added and stirred evenly. 132 g of bis[3-(trimethoxysilyl)propyl]amine and 54 g of triethylamine were added, and the mixture was reacted at 60° C. for 12 h. The mixture was extracted with chloroform and deionized water, and the organic phase was concentrated and dried to obtain an alkenyl cyanosiloxane monomer.
[0037] (2) Under a nitrogen atmosphere, 55 g of nano-SiO2, 440 mL of ethanol and 110 mL of deionized water were added to a reaction flask. After uniform dispersion, 3.3 g of vinyl cyanosiloxane monomer was added, and the pH of the system was adjusted to 3 with glacial acetic acid. The reaction was carried out at 60 °C for 9 h. After filtering, washing and drying under reduced pressure, vinyl cyanide-modified SiO2 was obtained.
[0038] (3) Add 4 g of sodium dodecyl sulfate and 200 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 20 g of vinyl acetate, 100 g of butyl acrylate, 8 g of acrylic acid, 12 g of sodium allyloxyhydroxypropyl sulfonate and 4 g of vinyl cyanide-modified SiO2, stir evenly at 70°C, add 3 g of a 10% by mass aqueous solution of ammonium persulfate dropwise, then react at 90°C for 3 h, cool to 50°C, add aqueous ammonia to adjust the pH to 8, and obtain a modified polyacrylic acid resin emulsion.
[0039] (4) 100 g of polyacrylate emulsion and 10 g of modified polyacrylic acid resin emulsion were added to a beaker, stirred at 1000 r / min for 5 min, 0.2 g of defoamer BYK-088, 15 g of terpene resin and 15 g of natural rubber emulsion were added, stirring was continued for 15 min, 0.1 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.05 g of preservative JB11 were added, and stirred evenly to obtain a sealing adhesive for packaging.
[0040] Example 3
[0041] (1) Under a nitrogen atmosphere, 20 g of α-cyanocinnamic acid, 240 g of thionyl chloride and 40 drops of N,N-dimethylformamide were added to a reaction flask, and the mixture was reacted at 60° C. for 5 h. Excess thionyl chloride was removed under reduced pressure, and then 300 mL of tetrahydrofuran was added and stirred evenly. 50 g of bis[3-(trimethoxysilyl)propyl]amine and 24 g of triethylamine were added, and the mixture was reacted at 40° C. for 24 h. The mixture was extracted with chloroform and deionized water, and the organic phase was concentrated and dried to obtain an alkenyl cyanosiloxane monomer.
[0042] (2) Under a nitrogen atmosphere, 15 g of nano-SiO2, 180 mL of ethanol and 45 mL of deionized water were added to a reaction flask. After uniform dispersion, 1.05 g of vinyl cyanosiloxane monomer was added, and the pH of the system was adjusted to 3 with glacial acetic acid. The reaction was carried out at 50 °C for 12 h. After filtering, washing and drying under reduced pressure, vinyl cyanide-modified SiO2 was obtained.
[0043] (3) Add 6 g of sodium dodecyl sulfate and 300 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 30 g of vinyl acetate, 100 g of butyl acrylate, 5 g of acrylic acid, 15 g of sodium allyloxyhydroxypropyl sulfonate and 6 g of vinyl cyanide-modified SiO2, stir evenly at 50°C, add 8 g of a 5% by mass aqueous solution of ammonium persulfate dropwise, then react at 75°C for 5 h, cool to 40°C, add aqueous ammonia to adjust the pH to 8, and obtain a modified polyacrylic acid resin emulsion.
[0044] (4) 100 g of polyacrylate emulsion and 15 g of modified polyacrylic acid resin emulsion were added to a beaker, stirred at 800 r / min for 10 min, 0.5 g of defoamer BYK-088, 20 g of terpene resin and 10 g of natural rubber emulsion were added, stirring was continued for 20 min, 0.3 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.08 g of preservative JB11 were added, and stirred evenly to obtain a sealing adhesive for packaging.
[0045] Example 4
[0046] (1) Under nitrogen atmosphere, 10 g of α-cyanocinnamic acid, 95 g of thionyl chloride and 13 drops of N,N-dimethylformamide were added to a reaction flask, and the mixture was reacted at 75° C. for 4 h. Excess thionyl chloride was removed under reduced pressure, and then 135 mL of tetrahydrofuran was added and stirred evenly. 23 g of bis[3-(trimethoxysilyl)propyl]amine and 10.5 g of triethylamine were added, and the mixture was reacted at 45° C. for 20 h. The mixture was extracted with chloroform and deionized water, and the organic phase was concentrated and dried to obtain an alkenyl cyanosiloxane monomer.
[0047] (2) Under a nitrogen atmosphere, 8 g of nano-SiO2, 92 mL of ethanol and 19.6 mL of deionized water were added to a reaction flask. After uniform dispersion, 0.64 g of vinyl cyanosiloxane monomer was added, and the pH of the system was adjusted to 4 with glacial acetic acid. The reaction was carried out at 60 °C for 9 h. After filtering, washing and drying under reduced pressure, vinyl cyano-modified SiO2 was obtained.
[0048] (3) Add 5 g of sodium dodecyl sulfate and 260 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 26 g of vinyl acetate, 100 g of butyl acrylate, 6 g of acrylic acid, 14 g of sodium allyloxyhydroxypropyl sulfonate and 8 g of vinyl cyanide-modified SiO2, stir evenly at 65°C, add 7 g of an 8% by mass aqueous solution of ammonium persulfate dropwise, then react at 85°C for 4 h, cool to 45°C, add aqueous ammonia to adjust the pH to 8, and obtain a modified polyacrylic acid resin emulsion.
[0049] (4) 100 g of polyacrylate emulsion and 20 g of modified polyacrylic acid resin emulsion were added to a beaker, stirred at 950 r / min for 7 min, 0.35 g of defoamer BYK-088, 18 g of terpene resin and 12 g of natural rubber emulsion were added, stirring was continued for 16 min, 0.2 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.07 g of preservative JB11 were added, and after stirring evenly, a sealing adhesive for packaging was obtained.
[0050] Example 5
[0051] (1) Under a nitrogen atmosphere, 30 g of α-cyanocinnamic acid, 270 g of thionyl chloride and 42 drops of N,N-dimethylformamide were added to a reaction flask, and the mixture was reacted at 80° C. for 5 h. Excess thionyl chloride was removed under reduced pressure, and then 405 mL of tetrahydrofuran was added and stirred evenly. 72 g of bis[3-(trimethoxysilyl)propyl]amine and 33 g of triethylamine were added, and the mixture was reacted at 55° C. for 24 h. The mixture was extracted with chloroform and deionized water, and the organic phase was concentrated and dried to obtain an alkenyl cyanosiloxane monomer.
[0052] (2) Under a nitrogen atmosphere, 25 g of nano-SiO2, 270 mL of ethanol and 65 mL of deionized water were added to a reaction flask. After uniform dispersion, 2.25 g of vinyl cyanosiloxane monomer was added, and the pH of the system was adjusted to 3 with glacial acetic acid. The reaction was carried out at 65 °C for 12 h. After filtering, washing and drying under reduced pressure, vinyl cyano-modified SiO2 was obtained.
[0053] (3) Add 5 g of sodium dodecyl sulfate and 240 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 23 g of vinyl acetate, 100 g of butyl acrylate, 7 g of acrylic acid, 13 g of sodium allyloxyhydroxypropyl sulfonate and 10 g of vinyl cyanide-modified SiO2, stir evenly at 65°C, add 6 g of 9% by mass ammonium persulfate aqueous solution dropwise, then react at 85°C for 4 h, cool to 45°C, add ammonia water to adjust the pH to 8, and obtain a modified polyacrylic acid resin emulsion.
[0054] (4) 100 g of polyacrylate emulsion and 25 g of modified polyacrylic acid resin emulsion were added to a beaker, stirred at 950 r / min for 10 min, 0.4 g of defoamer BYK-088, 18 g of terpene resin and 15 g of natural rubber emulsion were added, stirring was continued for 20 min, 0.3 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.08 g of preservative JB11 were added, and stirred evenly to obtain a sealing adhesive for packaging.
[0055] Comparative Example 1
[0056] (1) Add 5 g of sodium dodecyl sulfate and 280 mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stir to dissolve, add 25 g of vinyl acetate, 100 g of butyl acrylate, 7 g of acrylic acid, 14 g of sodium allyloxyhydroxypropyl sulfonate, 2 g of α-cyanocinnamic acid and 2 g of nano-SiO2, stir evenly at 60°C, dropwise add 5 g of an 8% by mass ammonium persulfate aqueous solution, then react at 85°C for 4 h, cool to 45°C, add aqueous ammonia to adjust the pH to 7, and obtain a modified polyacrylic acid resin emulsion.
[0057] (2) Add 100 g of polyacrylate emulsion and 5 g of modified polyacrylic acid resin emulsion into a beaker, stir at 900 r / min for 8 min, add 0.3 g of defoamer BYK-088, 18 g of terpene resin and 12 g of natural rubber emulsion, continue stirring for 16 min, add 0.2 g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.06 g of preservative JB11, stir evenly to obtain a sealing glue.
[0058] Comparative Example 2
[0059] Add 105g of polyacrylate emulsion into a beaker, stir at 900r / min for 8min, add 0.3g of defoamer BYK-088, 18g of terpene resin and 12g of natural rubber emulsion, continue stirring for 16min, add 0.2g of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene in a mass ratio of 1:1 and 0.06g of preservative JB11, stir evenly to obtain a sealing glue.
[0060] Sealing adhesive bonding performance test: The prepared sealing adhesive latex is evenly coated on BOPP (biaxially oriented polypropylene film) reinforced with plain glass cloth by a coater, and fully dried to make a tape, and its bonding performance is tested. The thickness of the adhesive layer after drying is strictly controlled to be 0.05mm; the 180° peel strength is tested according to GB / T2792-2014 standard; the shear strength is tested according to GB / T7754-1987 standard, and the initial adhesion is tested according to GB / T4852-2002 standard; the tensile testing machine used is an electronic universal testing machine, and the average value is taken after 5 measurements.
[0061] Table 1 Adhesion performance test
[0062]
[0063]
[0064] The unit "#" of initial adhesion represents the weight of the steel ball used in the rolling ball ramp stop test. Generally speaking, the larger the size of the steel ball, the stronger its initial adhesion. It can be seen from the test results in the above table that with the increase of the content of the modified polyacrylic acid resin emulsion, the bonding performance of the sealing glue gradually increases. Among them, the 180° peel strength in Example 4 is 26.50N / 25mm, and the shear strength is 0.479MPa. The initial adhesion and the lasting adhesion are both good. This is because on the one hand, the modified nano-SiO2 in the modified polyacrylic acid resin emulsion has a special structural hierarchy, showing a special quantum size effect and surface effect, with a large specific surface area, high surface energy and surface binding energy, which can increase the cohesive strength of the sealing glue. At the same time, because the modified nano-SiO2 is chemically bonded to the acrylic monomer, it can be stably stored. The inside of the sealing glue has good bonding properties. When subjected to external stress, it can inhibit crack growth, thereby greatly improving the bonding performance of the sealing glue. On the other hand, due to the functional monomers with functional groups such as carboxyl, sulfonic acid, and cyano in the polyacrylate emulsion, they can generate hydrogen bonds with the surface of the substrate after polymerization and undergo a certain degree of cross-linking, which greatly improves the cohesive strength and bonding performance of the polymer. At the same time, cyano is a strong polar group with great molecular polarity and intermolecular attraction. After the cyano group is introduced into the polyacrylate emulsion, intermolecular hydrogen bonds can be formed, which appropriately increases toughness and improves its bonding strength, so that the prepared sealing glue can be used in more packaging occasions.
[0065] The nano-SiO2 in Comparative Example 1 is not modified and is prone to agglomeration in the polyacrylate emulsion, which seriously affects its performance and makes the bonding performance of the sealing glue inferior to that of the embodiment; Comparative Example 2 does not contain strongly polar cyano groups and nano-SiO2, but is only an ordinary polyacrylate emulsion, and has the worst bonding performance.
[0066] Temperature resistance test: The prepared sealing latex was evenly coated on a polytetrafluoroethylene plate, placed horizontally, and dried naturally. After being placed at room temperature for 2 weeks, it was cut into dumbbell-shaped specimens and subjected to a tensile strength test according to GB / T 528-2009. The tensile speed was 50 mm / min and the test temperature was 25°C. Then, it was placed in a -20°C refrigerator and a 60°C oven for aging for 48 hours respectively, and the tensile strength test was conducted again.
[0067] Table 2 Temperature resistance test
[0068]
[0069] It can be seen from the test results in the above table that with the increase of the content of modified polyacrylic resin emulsion, the temperature resistance of the sealing glue gradually increases, and the tensile strength at a low temperature of -20°C and a high temperature of 60°C does not change significantly compared with that at room temperature. This is because, on the one hand, in the formula of the sealing glue of the present application, some natural rubber emulsion is appropriately added, and there are a large number of double bonds and hydrogen bonds in its molecular chain, which can react with the functional groups on the non-polar substrate to form a strong chemical bond, which can improve the high and low temperature aging performance of the sealing glue; on the other hand, the surface of the nano-SiO2 modified by the vinyl cyanosiloxane monomer constitutes a soft interface layer, and its compatibility with the polymer matrix is significantly improved, and it can be better dispersed and stably present. When subjected to external temperature changes, it can absorb deformation energy under stress and promote the brittle-tough transition of the matrix, thereby having an enhancing and toughening effect, which helps to improve the high and low temperature resistance of the sealing glue.
[0070] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a sealing adhesive for packaging, characterized in that: The preparation method is carried out according to the following steps: Step (1), adding 4-6g of sodium dodecyl sulfate and 200-300mL of deionized water to a reaction flask equipped with a reflux condenser and a dropping funnel, stirring to dissolve, adding 20-30g of vinyl acetate, 100g of butyl acrylate, 5-8g of acrylic acid, 12-15g of sodium allyloxyhydroxypropyl sulfonate and 2-10g of vinyl cyanide modified SiO2, stirring evenly at 50-70°C, adding 3-8g of ammonium persulfate aqueous solution dropwise, then reacting at 75-90°C for 3-5h, cooling to 40-50°C, adding ammonia water to adjust the pH to 7-8, and obtaining a modified polyacrylic acid resin emulsion; Step (2), adding 100g of polyacrylate emulsion and 5-25g of modified polyacrylic acid resin emulsion into a beaker, stirring at 800-1000r / min for 5-10min, adding 0.2-0.5g of defoamer, 15-20g of terpene resin and 10-15g of natural rubber emulsion, continuing stirring for 15-20min, adding 0.1-0.3g of wetting agent and 0.05-0.08g of preservative, stirring evenly, and obtaining a sealing adhesive for packaging.
2. The method for preparing the sealing adhesive for packaging according to claim 1, characterized in that: The mass fraction of the ammonium persulfate aqueous solution in step (1) is 5-10%.
3. The method for preparing the sealing adhesive for packaging according to claim 1, characterized in that: In the step (2), the wetting agent is a mixture of sodium diisopropylnaphthalene sulfonate and alkylphenol polyoxyethylene ether in a mass ratio of 1:
1.
4. The method for preparing the sealing adhesive for packaging according to claim 1, characterized in that: The main component of the natural rubber latex in step (2) is cis-1,4-polyisoprene, accounting for 91-94%.
5. The method for preparing the sealing adhesive for packaging according to claim 1, characterized in that: The preparation method of alkenyl cyanide modified SiO2 in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add α-cyanocinnamic acid, thionyl chloride and 1-2 drops of N,N-dimethylformamide to a reaction flask, react at 60-80° C. for 2-5 hours, remove excess thionyl chloride under reduced pressure, then add tetrahydrofuran and stir evenly, add bis[3-(trimethoxysilyl)propyl]amine and triethylamine, stir and react, after the reaction is completed, extract with chloroform and deionized water, concentrate the organic phase, and dry to obtain an alkenyl cyanosiloxane monomer; Step S2, under a nitrogen atmosphere, add nano-SiO2, ethanol and deionized water to a reaction flask, and after uniform dispersion, add vinyl cyanosiloxane monomer, adjust the system pH to 3-5 with glacial acetic acid, stir and react, and after the reaction is completed, filter, wash, and dry under reduced pressure to obtain vinyl cyanide-modified SiO2.
6. The method for preparing the sealing adhesive for packaging according to claim 5, characterized in that: In the step S1, the ratio of Α-cyanocinnamic acid, thionyl chloride, tetrahydrofuran, bis[3-(trimethoxysilyl)propyl]amine, and triethylamine is 1 g:(8-12) g:(10-15) mL:(2.2-2.5) g:(0.9-1.2) g.
7. The method for preparing the sealing adhesive for packaging according to claim 5, characterized in that: In step S1, the reaction temperature is 40-60° C. and the reaction time is 12-24 h.
8. The method for preparing the sealing adhesive for packaging according to claim 5, characterized in that: In the step S2, the ratio of nano-SiO2, ethanol, deionized water, and vinyl cyanosiloxane monomer is 1 g: (8-12) mL: (2-3) mL: (0.05-0.09) g.
9. The method for preparing the sealing adhesive for packaging according to claim 5, characterized in that: In step S2, the reaction temperature is 50-65° C. and the reaction time is 5-12 h.
10. A sealing adhesive for packaging, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sealing adhesive and preparation method thereof
CN102533181B